Pendampingan Mahasiswa Kuliah Kerja Nyata (KKN) Dalam Meningkatkan Kualitas Pendidikan Al-Qur’an Sebagai Wujud Pengabdian Di Kampung Cibodas, Desa Cimacan Kabupaten Cianjur - Tsauri, Ahmad Latif; Maulana, Ridwan; Amal, Gilang Dzikrul; Al-Farisi, Muhammad Salman; Al-Qowi, Muhammad Alam (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2025)
The purpose of this paper is to describe the role of Real Work Lecture (KKN) students in Cibodas Village, Cimacan Village, Cianjur Regency in helping to improve the quality of Qur'an education. The results of the discussion showed that KKN students made a real contribution to helping to improve the Qur'an learning system in the community, one of which was through the Al-Qur'an Education Park activities, tajweed and tahsin training, and teacher coaching. In addition to helping teach children how to read the Qur'an, the activity also strengthens the relationship between students and the surrounding community. Therefore, this paper provides an overview that the KKN program is a real part of the education of Islamic students in the development of religious education in the community.